Isolation and Characterization of a Gene Coding for Chitinase in Developing Winged Bean Seed (Psophocarpus Tetragonolubus ) - Sekeli, Rogayah (2000)
Chitinase, which catalyse the hydrolysis of the β-1,4-N-acetyl-D-glucosamine linkages of the fungal cell wall polymer chitin, is involved in inducible defences of plants. The aim of this research is to isolate a chitinase genes from seed of winged bean. In order to isolate genes encoding for chitinases from a cDNA library of winged bean seed, two sets of degenerate primers were designed which corresponded to conserved regions of chitinases class I and class IV. These were then reverse transcribed and subsequently amplified using polymerase chain reactions (RT -PCR) using 4 weeks old seeds cDNA as template. A 1.1 kb fragment was cloned, and subjected to terminal sequence analysis to verify the presence of sequences encoding for chitinases. Nucleotide sequence analysis showed that the fragment appears to encode for a class I chitinase, and this fragment was then used as a probe to screen for a full length gene from the winged bean seed cDNA library. After library screening one clone, CHRZP was isolated and found to encode a chitinase gene. The complete nucleotide sequence of the winged bean chitinase (1324 bp) encoded a polypeptide of 289 amino acids that encodes for a basic chitinase with cysteine-rich domain at the N-terminal. A Comparison of amino acid sequence showed 88% similarity to a chitinase sequence isolated from Oryza sativa. RNA blot hybridisation revealed that mRNA that corresponded to CHRZP accumulates to high levels in leaves compared to seed, tuber and pod with a transcript size of 1.0 kb. Southern hybridisation analysis indicated that this gene was present as a single copy gene in the winged bean genome.